Production and loss rates of picocyanobacteria in tropical coastal waters / Heng Pei Li - Heng, Pei Li (2014)
We studied temporal variation of picocyanobacteria and their production (μ) and loss (g) rates for over two years of period at Port Klang (PK) estuarine waters [03º00.1'N, 101º23.4'E] and Port Dickson (PD) coastal waters [02º29.5'N, 101º50.3'E] along the Straits of Malacca. PK waters showed higher level of eutrophication, lower euphotic depth and higher TSS level as compared to PD. Heterotrophic bacterial abundance at PK (2.78 ± 1.58 × 106 cell ml–1) was generally higher than PD (1.39 ± 0.49 × 106 cell ml–1) (Student’s t-test: t = – 5.30, df = 47, p < 0.001). In contrast, picocyanobacterial abundance at PD (1.33 ± 0.47 × 105 cell ml–1) was always higher than at PK (0.28 ± 0.17 × 105 cell ml–1) (Student’s t-test: t = 10.44, df = 30, p < 0.001). μ and g of picocyanobacteria were tightly coupled with each other (R2 = 0.47, df = 459, p < 0.001) and similar at both sites (p > 0.05). μ ranged from – 0.03 to 1.57 d–1 while g ranged from 0.12 to 1.80 d–1 at PK whereas at PD, μ and g averaged at 0.99 ± 0.28 d–1 and 0.83 ± 0.42 d–1, respectively. Temperature limitation was weak at both sampling sites (p > 0.05) but there was tight coupling between Secchi depth and abundance of picocyanobacteria at both sites (R2 = 0.43, df = 45, p < 0.01). Picocyanobacterial abundance also decreased with increasing siltation (R2 = – 0.70, df = 45, p < 0.01) which suggested light availability as a factor for picocyanobacteria distribution. Via a two-factorial experiment, we showed that light had a significant effect on production but only at PD (F = 5.94, p < 0.05) whereas nutrient enrichment was not an important factor. The contribution of picocyanobacteria to total primary production and net production was also higher at PD which suggested that at PD, environmental conditions were more favourable towards picocyanobacteria as compared to PK.